Effectiveness of Music and Aromatheraphy as an Intervention for Preoperative Anxiety: A Systematic Review - Pratiwi, Rizky Intan; Astriani, Lelli; Hutapea, Dwight Mahaputera Marulitua; Hutapea, Albert Manggading (11th International Scholars Conference, 2018)
Anxiety is a serious condition among preoperative patients. The prevalence of preoperative anxiety disorder in Indonesia is around 6-7% of the general population. A systematic review was conducted from an online database such as EBSCO, CINAHL, Science Direct, ProQuest, E-Journal. Eighteen studies of music and aromatherapy for perioperative anxiety met the inclusion and exclusion criteria. Eleven studies from 1995 to 2018 indicated a significant effect of music on the reduction of anxiety levels of preoperative patients. Seven studies from 2008 to 2017 showed that aromatherapy exerted a significant effect as an intervention to reduce the level of anxiety among preoperative patients. When comparing the effects of music and aromatherapy, there was no statistically significant difference in the anxiety level between the experimental group and the control group with the combination of music and aromatherapy in experimental and control groups as the intervention. It was concluded that music and aromatherapy are an effective intervention to reduce anxiety for perioperative procedures among patients.